Can't change my political disaffection! The role of political disaffection, trust, and resistance to change in internet voting. Issue 2 (13th March 2020) - Sharma, Shwadhin
Abstract : Purpose: This paper aims to put the focus on political disaffection that the voters may have and its impact on their resistance to the changes, thereby influencing intention to adopt Internet voting. This study also examines the impact of perceived risk and technological skills on the trust of the Internet technology and informal networks, such as social influence and media influence on the trust of the government. Design/methodology/approach: To empirically test the model, an online survey is administered to 851 people who are eligible to vote. Findings: The findings show that positive media influence and social influence also significantly impact trust in government but trust in government does not necessarily decrease resistance to change and positively impact intention to adopt eVoting. Also, the resistance to change was shown to significantly influence the intention to use Internet voting. Research limitations/implications: A primary potential limitation of this study is the use of convenience sampling, which may lead to self-selection bias that limits the generalization of our research to all citizens. Practical implications: Government institutions, as well as political parties, can use the findings of this research to understand how political dissatisfaction such as apathy and cynicism can increase trust in technology and lead to higher participation in online voting. Originality/value: While the focus on previous literature has been heavily on security and system requirements, this study expands existing research by exploring voting habits, political disaffection, the resistance of change and informal influence on intention to use online voting.